A Study of Tibial Nerve in the Popliteal Fossa Along With Its Variations in Its Branching Pattern - W Benjamin; Raghavendra V Pisale; SA Premchand; Edward Indla; Seema Valsalan Ennazhiyil; VR Akshara; Lovely S Livingston (Academia Anatomica International, 2020)
Background: A detailed Knowledge of these variations in motor branching patterns will help the surgeons when certain procedures are done for calf reduction and also when selective neurectomy is required. It is also required by the anesthetists to give neurolytic blocks. Subjects and Methods: 40 formalin-fixed lower limbs of adult human cadavers were selected. The origin of the tibial nerve, variations in a branching pattern, number of muscular branches given was studied by dissection. The Level of origin of these nerves was taken to the apex of the head of the fibula (AHF). Results: In 70 % of specimens the origin of the Tibial Nerve was < 12 cm and in 30 % it was between 12-24 cm above the level of AHF. In 10% of cases, the sural nerve originated from the nerve to the medial head of gastrocnemius (MHG). In 82.5% of specimens, the MHG received one branch from the tibial nerve and in 17.5% it received two branches. The lateral head of Gastrocnemius (LHG) received one branch from the tibial nerve. In 10%, there was a common branch for the LHG and the soleus muscle. 90% of specimens had one branch and 10% had two branches that supplied the soleus muscle. A single branch supplied the plantaris muscle. The popliteus muscle also received a single branch. Conclusion : The results in the study provide information that is required by the anatomists, surgeons, radiologists and anesthetists.